Chemospecific Intramolecular Buchner Reaction Catalyzed by Copper(II) Acetylacetonate. Issue 6 (3rd April 2014) - Mo, Shanyan; Xu, Jiaxi
Abstract A chemospecific intramolecular Buchner reaction of N‐benzyl‐2‐cyano‐2‐diazoacetamides catalyzed by inexpensive copper(II) acetylacetonate (acac) has been achieved to synthesize a variety of 9‐aza‐1‐cyanobicyclo[5.3.0]deca‐2, 4, 6‐trien‐10‐ones, 5, 7‐bicyclic products. The methodology involves sole chemoselectivity, an inexpensive metal catalyst, broad substrate scope, and moderate to excellent yields.